National Health IT Services in Finland - Saranummi, N.; Ensio, A.; Laine, M.; Nykänen, P.; Itkonen, P. (Methods of Information in Medicine, 2007)
Objectives: In 2002 a decision was reached to set up a nation-wide electronic health record system in Finland. The legal framework of actors with the necessary mandate was approved in the parliament in December 2006. A set of standards and norms have been selected that all health care actors need to follow. Functional specifications of the services were completed in 2006. Setting up the centralized health IT services begins in 2007.Centralization of patient record data allows the reorganization of health service providers to take place at local and regional levels according to need. The services allow users to access patient records securely from anywhere with the provision that they have the right to access private patient data.Methods: The functionality of the services and the necessary infrastructure has been agreed to in projects and working groups involving users, experts, key stakeholders and vendors.Results: The legal framework was approved in the parliament in December 2006. The functional specifications of thecentralized health IT services were finalized in 2006.Conclusions: The implementation of the services will start in 2007.
Keywords: Health information infrastructure; electronic patient record; interoperability; archive; architecture